2016
DOI: 10.1038/srep34627
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Management for Improving Growth and Grain Yield of Maize (Zea mays L.) under Moisture Stress Condition

Abstract: Potassium (K) fertilizer management is beneficial for improving growth, yield and yield components of field crops under moisture stress condition in semiarid climates. Field experiments were conducted to study the response of maize (Zea mays L., cv. Azam) to foliar and soil applied K during summer 2013 and 2014. The experiments were carried out at the Agronomy Research Farm of The University of Agriculture Peshawar, Northwest Pakistan under limited irrigation (moisture stress) condition. It was concluded from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 29 publications
(22 reference statements)
6
52
0
6
Order By: Relevance
“…Hussain et al [21] reported a significant interaction between mung bean genotypes and potassium application with respect to protein content and seed yield. Amanullah et al [24] reported that foliar and soil applied potassium improved maize performance under moisture stress. Nevertheless, there is a limited research on interactive response of potassium application and maize genotypes to water stress for yield related traits and drought susceptibility index especially under arid conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Hussain et al [21] reported a significant interaction between mung bean genotypes and potassium application with respect to protein content and seed yield. Amanullah et al [24] reported that foliar and soil applied potassium improved maize performance under moisture stress. Nevertheless, there is a limited research on interactive response of potassium application and maize genotypes to water stress for yield related traits and drought susceptibility index especially under arid conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the effect of potassium on total phenolic content in potato tubers, illustrated results showed that the healthy plants (higher yield) which received 120 kg/feddan had the lowest phenolic content, while the control plants had the highest values, which may indicate that the control plants might be subjected to stress during the growing seasons. This effect may be attributed to the role of potassium in alleviation of abiotic stress (Cakmak, 2005;Amanullah and Irfanullah, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Cutcliffe and Munro (1976) reported a slight early season advantage from high rate of potassium. One the other hand, Pettigrew (2003) and Amanullah et al (2016) stated that the earlier crop maturity of cotton and maize was associated with low dose of potassium. While, Abay and Sheleme (2011) confirmed that potassium application has no effect on physiological maturity of potato.…”
Section: Accordingmentioning
confidence: 99%
“…-Leaf proline content, in µg/g fresh weight, according to Bates et al (1973). -Potassium, sodium contents and Na + /K + ratio in plants leaves as mmole/kg dry weight, according to Allen et al (1974). At harvest time, yield and yield components were determined for each crop under study as well as potassium and protein percentage in grains and/or seeds, according to Horneck and Miller (1998).…”
Section: • T2-t1= Number Of Days Between Two Successive Samples (Day)mentioning
confidence: 99%